Computer-supported Techniques to Increase Students Engagement in Programming - Tavares, Paula Correia (2017)
One of the main reasons that justify the student’s failure in (introductory) programming courses is the lack of motivation that impacts on the knowledge acquisition process, affecting learning results. As soon as students face the difficulties concerning the development of algorithms or the coding in a programming language, they give up and do not try harder to solve other problems; they think it is a demanding activity and feel frustrated. In this paper we describe in detail an experiment conducted to verify the effectiveness, in terms of the increase in motivation and in knowledge acquisition, of combining program Animation tools with the immediate feedback provided by Automatic Evaluations Systems.